Antagonist Anti-CD28 Therapeutics for the Treatment of Autoimmune Disorders - Bernard Vanhove; Nicolas Poirier; Fadi Fakhouri; Laetitia Laurent; Bert ’t Hart; Pedro H. Papotto; Luiz V. Rizzo; Masaaki Zaitsu; Fadi Issa; Kathryn Wood; Jean-Paul Soulillou; Gilles Blancho (Antibodies, 2017)
The effector functions of T lymphocytes are responsible for most autoimmune disorders and act by directly damaging tissues or by indirectly promoting inflammation and antibody responses. Co-stimulatory and co-inhibitory T cell receptor molecules are the primary pharmacological targets that enable interference with immune-mediated diseases. Among these, selective CD28 antagonists have drawn special interest, since they tip the co-stimulation/co-inhibition balance towards efficiently inhibiting effector T cells while promoting suppression by pre-existing regulatory T-cells. After having demonstrated outstanding therapeutic efficacy in multiple models of autoimmunity, inflammation and transplantation, and safety in phase-I studies in humans, selective CD28 antagonists are currently in early clinical development for the treatment of systemic lupus erythematous and rheumatoid arthritis. Here, we review the available proof of concept studies for CD28 antagonists in autoimmunity, with a special focus on the mechanisms of action.